Implementing Educational functions of Green Campus on Environmental Education Course - Syafii, Wan; Putra, Riki Apriyandi (Proceedings of the UR International Conference on Educational Sciences, 2018)
The objective of this research was to find out the implementation of Educational functions of Green Campusin enhancing studentsâ scientific attitude on environmental education course. This research was a Descriptive Research. There were two study programs involved in it, namely Mathematic Education Study Program that consisted of 40 students, and Pancasilaand Civic Educationstudy Program which consisted of 37 students. The data of this research were taken from the analysis of questionnaire, observation, and interview. The result showed that there wasan enhancement of studentsâ scientific attitude. The highest enhancement of their scientific attitude can be seen from the following indicators sequentially:a)encouraging the curiosity is at 96.10%, b)prioritizing the proof and be skeptical is at 92.21%, c)can work togetheris at 81.82%, d)be positive towards failureis at 74.03%, and e) accepting differences is at 72.73%.The result of observation and Interview asserts that the students were very enthusiastic in understanding the environmental concepts and conservation efforts based on local culture.